Identification of the nymphal stages of two European seed bugs, L. equestris and L. simulans (Hemiptera: Heteroptera: Lygaeidae), using DNA barcodes - Lis, Barbara; Lis, Jerzy A.; Ziaja, Dariusz J. (Zootaxa, 2013)
The genus Lygaeus Fabricius, 1794 includes more than fifty species, mainly distributed in the Old World regions, with 17 species known from the Palearctic (Péricart 2001; Wachmann et al. 2007), and only two from Central Europe, i.e., L. equestris (Linnaeus, 1758) and L. simulans Deckert, 1985 (Péricart 2001).